2016
DOI: 10.1073/pnas.1602012113
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal genomes interplay through phosphoinositol 3-kinase(PI3K)-p110α signaling to modify placental resource allocation

Abstract: Pregnancy success and life-long health depend on a cooperative interaction between the mother and the fetus in the allocation of resources. As the site of materno-fetal nutrient transfer, the placenta is central to this interplay; however, the relative importance of the maternal versus fetal genotypes in modifying the allocation of resources to the fetus is unknown. Using genetic inactivation of the growth and metabolism regulator, Pik3ca (encoding PIK3CA also known as p110α, α/+), we examined the interplay be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 55 publications
10
61
0
Order By: Relevance
“…At E11.5 homozygous embryos were smaller, with poorly developed limb buds and reduced eye pigmentation ( Figure 1A ), while heterozygous embryos were smaller from E15.5 onwards ( Supplemental Figure S2 ). No difference in mass of wild type and heterozygous placentas examined from wild type dams was seen, however vascularisation of the placental exchange region was severely compromised, with around a 40% reduction in vessel density, volume and length at E15.5 (Supplemental Figure S3), as reported previously for placentas heterozygous for a kinase dead p110α catalytic subunit (28). In contrast to that model, however, the size of the placental exchange region (both volume and surface area) and the thickness of the diffusion barrier were normal ( Supplemental Figure S3 ).…”
Section: Resultssupporting
confidence: 79%
“…At E11.5 homozygous embryos were smaller, with poorly developed limb buds and reduced eye pigmentation ( Figure 1A ), while heterozygous embryos were smaller from E15.5 onwards ( Supplemental Figure S2 ). No difference in mass of wild type and heterozygous placentas examined from wild type dams was seen, however vascularisation of the placental exchange region was severely compromised, with around a 40% reduction in vessel density, volume and length at E15.5 (Supplemental Figure S3), as reported previously for placentas heterozygous for a kinase dead p110α catalytic subunit (28). In contrast to that model, however, the size of the placental exchange region (both volume and surface area) and the thickness of the diffusion barrier were normal ( Supplemental Figure S3 ).…”
Section: Resultssupporting
confidence: 79%
“…Experiments based on genetic and dietary manipulations have demonstrated that the placenta interprets fetal and maternal interests, adapting its phenotype and function according to resource availability [7274]. An example of these fascinating adaptations is that undernourished placentas can overcome MFR and maintain or even increase their nutrient transfer capacity to help maintain fetal growth [50].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT signaling has been shown to play a role in trophectoderm migration [40] and placental resource allocation [41], as well as being implicated in embryonic neurogenesis and angiogenesis [40, 42]. Many of these pathways also work in conjunction with one another; the PI3K and prolactin signaling pathways have been shown to increase pancreatic islet mass and sensitivity to glucose during pregnancy [43]; likely influencing insulin receptor signaling, another affected pathway, simultaneously.…”
Section: Discussionmentioning
confidence: 99%